Evaluation of long-term welfare initiatives on working equid welfare and social transmission of knowledge in Mexico. - Emily Haddy; Faith Burden; José Antonio Fernando-Martínez; Dafne Legaria-Ramírez; Zoe Raw; Julia Brown; Juliane Kaminski; Leanne Proops (PLoS ONE, 2021)
Working equids play an essential role in supporting livelihoods, providing resilience and income security to people around the world, yet their welfare is often poor. Consequently, animal welfare focussed NGOs employ a range of initiatives aimed at improving standards of working equid welfare. However, there is debate surrounding the efficacy of welfare initiatives utilised and long term monitoring and evaluation of initiatives is rarely undertaken. This study compares equid welfare and the social transmission of welfare information across Mexican communities that had previously received differing intervention histories (veterinary treatment plus educational initiatives, veterinary treatment only and control communities) in order to assess their efficacy. Indicators of equid welfare were assessed using the Equid Assessment Research and Scoping tool and included body condition score, skin alterations, lameness, general health status and reaction to observer approach. Owners were interviewed about their involvement in previous welfare initiatives, beliefs regarding equid emotions and pain, and the social transmission of welfare knowledge, including whether they ask advice about their equid or discuss its health with others and whether there is a specific individual that they consider to be 'good with equids' in their community. In total 266 owners were interviewed from 25 communities across three states. Better welfare (specifically body condition and skin alteration scores) was seen in communities where a history of combined free veterinary treatment and educational initiatives had taken place compared to those that had only received veterinary treatment or control communities. The social transfer of welfare knowledge was also higher in these communities, suggesting that the discussion and transfer of equid welfare advice within communities can act as a mechanism to disseminate good welfare practices more widely. Our results suggest that using a combined approach may enhance the success of welfare initiatives, a finding that may impact future NGO programming.